Characterization of the environmental fragility of a urban river basin in the municipality of Santa Maria – RS - Schiavo, Bruna Nascimento de Vasconcellos; Hentz, Ângela Maria Klein; Corte, Ana Paula Dalla; Sanquetta, Carlos Roberto (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
The Geoprocessing has been considered a fundamental tool in the definition of intervention policies and environmental management. This work presents a methodological guide of application of Geoprocessing technologies to characterize the environmental fragility of Arroio Cadena sub river basin, inserted in the municipality of Santa Maria, central region of Rio Grande do Sul state. We used the methodology proposed by Ross in (1994), which is based in the comprehension of the characteristics and the dynamics of the natural environment. To evaluate the fragility, it is established weights or grades to each situation that the variables can present. We used as indicators of the potential environmental fragility, the factors: declivity and soil type, and as indicators of emerging fragility, the factors: declivity, soil type and the use and occupation of the land. Among the uses of the basin, the areas of soil that is exposed and urbanization predominate. The basin has a weak potential fragility, with 52.9% in relation to the total area, and it is a consequence of the flat declivity aggregated in the soil type. It presents a strong emerging fragility, with 37.7% of the total area, due to the irregular occupations and the inadequate use of natural resources.